The Influence of Parent’s Perception and Involvement in Purchasing Decision of Toys For Children - Milatul Ulfa; Moh Djemjem Djamaludin (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2016)
Toys are